2009
DOI: 10.1681/asn.2008070734
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidized LDL Modulates Apoptosis of Regulatory T Cells in Patients with ESRD

Abstract: Increased levels of oxidized low-density lipoproteins (oxLDL) contribute to the increased risk for atherosclerosis, which persists even after adjusting for traditional risk factors, among patients with ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…Indeed, these individuals show features 50 and maximum suppression of chronic inflammation/immune dysregulation (25)(26)(27). Although some of the chronic inflammation is attributable to excessive immune system activation (37), abnormalities in Tregs have also been described, particularly a defect in Treg numbers and function (28,38); some of this defect is ascribed to high apoptosis in the presence of uremic factors, particularly oxidized LDL (38). However, these studies did not include strict age and sex matching of patients to controls (one of them did not include HCs at all) (28), included patients with immunologic and inflammatory diseases (28), and did not address important phenotypic characteristics required of Tregs for cell-based therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these individuals show features 50 and maximum suppression of chronic inflammation/immune dysregulation (25)(26)(27). Although some of the chronic inflammation is attributable to excessive immune system activation (37), abnormalities in Tregs have also been described, particularly a defect in Treg numbers and function (28,38); some of this defect is ascribed to high apoptosis in the presence of uremic factors, particularly oxidized LDL (38). However, these studies did not include strict age and sex matching of patients to controls (one of them did not include HCs at all) (28), included patients with immunologic and inflammatory diseases (28), and did not address important phenotypic characteristics required of Tregs for cell-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that patients on HD have equivalent Treg subsets I and III to their matched controls and express almost identical Treg surface markers on these subsets (CD27, CD39, HLA-DR, and FOXP3). Population II Tregs are effector Tregs, with potent suppressive function, that die quickly on activation (14), and therefore, the deficiency of population II observed in HD patients may be the result of increased apoptosis (38) or impaired generation of effector Tregs in the context of chronic inflammation. In either case, population II does not expand ex vivo and therefore, is not amenable to use for cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The CKD/ESRD-induced systemic inflammation is caused by activation of the innate and adaptive immune responses and impairment of the anti-inflammatory regulatory factors, events that are mediated by the following: (1) accumulation of proinflammatory oxidized low-density lipoprotein coupled with the deficiency of high-density lipoprotein and its reduced anti-inflammatory capacity 36,37 ; (2) disruption of the intestinal epithelial barrier structure and altered intestinal microbiome, which promote systemic inflammation by enabling influx of endotoxin and other noxious products in the systemic circulation 38 ; (3) increased population and sustained activation of monocytes, which is marked by their increased basal expressions of integrins, Toll-like receptors 2 and 4, and spontaneous production of cytokine and reactive oxygen species 39,40 ; (4) impaired inhibitory activity and a reduced population of regulatory T lymphocytes, which are essential for mitigating inflammation 41 ; (5) spontaneous activation, degranulation, and increased basal production of ROS by circulating polymorphonuclear leukocytes (PMNs) 39 ; (6) increased ROS production and chemokine expression by the cellular constituents of various tissues 10,41,42 ; and (7) co-existing conditions such as autoimmune diseases and diabetes.…”
Section: Contribution Of Iron Overload To Systemic Inflammation and Imentioning
confidence: 99%
“…In chronic kidney disease (CKD), all immune effector cells appear to be affected. For example, monocytes have an activated phenotype [5], polymorphonuclear leukocytes have a decreased phagocytic capacity [6], the CD4/CD8 T cell ratio is decreased [7], functional defects in regulatory T cells have been demonstrated [8], and B cells [9] as well as natural killer (NK) cells [10] are decreased. One major mediator of these abnormalities is the overproduction of reactive oxygen species (ROS), which is a hallmark of CKD-associated inflammation.…”
Section: Introductionmentioning
confidence: 99%